Pengaruh Kegiatan Ninja Warrior Kids Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Yayasan Amalan Kota Padang - Syovianti, Rahma; Anggraini, Vivi; Mayar, Farida; Yeni, Indra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to determine the effect of Ninja Warrior Kids activities on gross motor development of children aged 5-6 years in learning activities at Amalan Foundation Kindergarten, Padang City. This study uses a quantitative approach with a quasi-experimental method. The population in this study were all Amalan Foundation Kindergarten students in the 2024/2025 school year. The sampling technique used was cluster sampling, with Bintang class as the experimental group (12 children) and Bulan class as the control group (12 children). The experimental group received treatment in the form of Ninja Warrior Kids activities, while the control group followed the traditional game of engklek. Data were obtained through pre-test and post-test which were analyzed using the independent sample t-test statistical test. The results showed that there was a significant influence between Ninja Warrior Kids activities on children's gross motor development. This is evidenced by the significance value (2-tailed) of 0.017 < 0.05. Thus, it can be concluded that Ninja Warrior Kids activities are effective as an alternative learning media to develop gross motor skills in early childhood. The findings of this research have significant implications for early childhood education, particularly in enhancing motor development through engaging physical activities. By integrating Ninja Warrior Kids activities into the curriculum, educators can promote physical activity that not only fosters gross motor skills but also encourages social interaction and teamwork among children. This experimental research highlights the importance of innovative approaches in early childhood education, suggesting that such activities can be a valuable addition to traditional learning methods